Assessment of the risk associated with Bacillus cereus isolates and potential combat with methanolic Artemisia vulgaris extract - Fareid, Mohamed A.; El-Sherbiny, Gamal M.; Elafandy, Nancy M.; Eltoum, Nagat E.; Othman, Mohamed S.; Sharaf, Mohamed H.; Abu-Elghait, Mohammed; Elkhashab, Dina M.; Hamada, Fatma A. (Frontiers in Microbiology, 2025)
IntroductionBacillus cereus (B. cereus) is widely distributed in natural environments, particularly in soil and plant matter, and is frequently linked to foodborne illness outbreaks, accounting for approximately 1.4%–12% of food poisoning cases worldwide. This study aimed to assess the presence of toxigenic and emetic genes among B. cereus isolates, evaluate their antibiotic susceptibility, and investigate the antimicrobial potential of Artemisia vulgaris (A. vulgaris) extract.MethodsPolymerase chain reaction (PCR) was employed to detect toxigenic and emetic genes in B. cereus isolates. Antibiotic susceptibility was tested against a panel of agents. The antimicrobial, antibiofilm, antioxidant, cytotoxic, and gene-suppressing activities of methanolic A. vulgaris extract were evaluated using standard microbiological, biochemical, and molecular assays. GC-MS and HPLC analyses were performed to identify major bioactive compounds.ResultsPCR revealed that the isolates harbored hemolysin BL (HBL) genes hblA (8.62%) and hblB (20.68%), non-hemolytic enterotoxin (NHE) genes nheA (20.68%) and nheB (22.41%), as well as bceT (29.30%) and ces (15.51%) genes associated with emetic toxin production. Antibiotic testing showed high sensitivity to ciprofloxacin (91.37%) and rifampicin (96.54%), but strong resistance to ampicillin (86.20%) and novobiocin (65.51%). A. vulgaris extract demonstrated potent antibacterial activity (inhibition zones: 19.20 ± 0.25 mm to 27.10 ± 0.13 mm; MICs: 62.5–250 μg/mL), significantly inhibited biofilm formation, and downregulated toxigenic genes by −2.5 to −5.2 fold (***P < 0.0001). The extract also displayed strong antioxidant activity (IC50: 12.7 μg/mL, DPPH; 14.2 μg/mL, ABTS) and low cytotoxicity (IC50: 524.7 ± 1.23 μg/mL, Vero cells; 236.5 ± 1.74 μg/mL, HFB4 cells). GC-MS identified dopamine N,N-dimethyl-dimethyl ether (40.31%) and n-hexadecanoic acid (16.57%) as major compounds, while HPLC revealed high levels of chlorogenic acid, luteolin, and quercitrin.Discussion/conclusionThese findings highlight the public health risks posed by toxigenic B. cereus in food contamination. The methanolic extract of A. vulgaris exhibits strong antibacterial, antibiofilm, antioxidant, and gene-suppressing activities, supporting its potential as a natural therapeutic strategy against B. cereus and its virulence factors.